Utilization of agro-industrial products for increasing red pigment production of Monascus purpureus AHK12 - Pongrawee Nimnoi" (Science Faculty of Chiang Mai University, 2019)
Natural pigments have been recently focused as an important alternative to harmful synthetic dyes. As the manufacturing process of natural pigments that is mainly based on the extraction from plant materials makes the market prices high, the present study aims to evaluate the potential of low-cost agricultural products as substrates for red pigment production of Monascus purpureus AHK12 by using solid-state fermentation for reducing the production cost. The result showed that corn meal was the best substrate for pigment production followed by bagasse and coconut residue, respectively, whereas soybean meal was not a suitable substrate. Additions of each of 4%, 6% and 8% glucose and molasses at the same concentrations potently improved the pigment yields. Corn meal supplemented with either 8% glucose or 8% molasses achieved the highest pigment yields up to 1.7-fold when compared with controls. Co-supplementations of either glucose or molasses with each of whey and soybean milk as nitrogen sources were also evaluated. Among all substrates tested, a co-supplementation of molasses and soybean milk conferred the highest pigment yield. Corn meal co-supplemented with 8% molasses and 1% soybean milk provided the highest pigment yields up to 5.94-fold when compared with the mere additions of 8% molasses and 8% glucose. The produced pigments were stable under high temperatures and long-time sunlight exposure, whereas they were degraded after long-time UV exposure. These properties suggest that Monascus pigments are applicably useful for thermal process that is significant for an industrial scale.